2019
DOI: 10.3390/molecules24081588
|View full text |Cite
|
Sign up to set email alerts
|

[1,2,5]Thiadiazolo[3,4-d]Pyridazine as an Internal Acceptor in the D-A-π-A Organic Sensitizers for Dye-Sensitized Solar Cells

Abstract: Four new D-A-π-A metal-free organic sensitizers for dye-sensitized solar cells (DSSCs), with [1,2,5]thiadiazolo[3 ,4-d]pyridazine as internal acceptor, thiophene unit as π-spacer and cyanoacrylate as anchoring electron acceptor, have been synthesized. The donor moiety was introduced into [1,2,5]thiadiazolo[3,4-d]pyridazine by nucleophilic aromatic substitution and Suzuki cross-coupling reactions, allowing design of D-A-π-A sensitizers with the donor attached to the internal heterocyclic acceptor not only by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The attachment of strong electron-withdrawing groups (i.e., fluorine) at positions 5 and 6 has produced many different materials derived from 5,6-difluoro-2,1,3-benzothiadiazole [ 13 ]. Recently, the synthesis of an ultra-high electron-deficient [1,2,5]thiadiazolo[3,4- d ]pyridazine system with the formal replacement of carbon atoms in the 5- and/or 6-positions by electronegative atoms nitrogen has been reported [ 19 ]; it has been shown to be an important intermediate for the synthesis of dyes with various possible applications [ 18 , 20 , 21 ]. A third way to increase the electron-withdrawing strength of the benzothiadiazole ring is heteroannelation at positions 5 and 6 to create an acceptor, such as benzo-[1,2- c :4,5- c ’]bis[1,2,5]thiadiazole (benzo-bis-thiadiazole, BBT), a sulfur–nitrogen heterocycle with the lowest LUMO energy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of strong electron-withdrawing groups (i.e., fluorine) at positions 5 and 6 has produced many different materials derived from 5,6-difluoro-2,1,3-benzothiadiazole [ 13 ]. Recently, the synthesis of an ultra-high electron-deficient [1,2,5]thiadiazolo[3,4- d ]pyridazine system with the formal replacement of carbon atoms in the 5- and/or 6-positions by electronegative atoms nitrogen has been reported [ 19 ]; it has been shown to be an important intermediate for the synthesis of dyes with various possible applications [ 18 , 20 , 21 ]. A third way to increase the electron-withdrawing strength of the benzothiadiazole ring is heteroannelation at positions 5 and 6 to create an acceptor, such as benzo-[1,2- c :4,5- c ’]bis[1,2,5]thiadiazole (benzo-bis-thiadiazole, BBT), a sulfur–nitrogen heterocycle with the lowest LUMO energy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…With an intention of further improving the optoelectronic attributes and thus the efficiency of the presynthesized DF-PCIC molecule, we have investigated the effect of insertion of different bridges in this study as shown in Figure . The six novel π-spacer/bridges inserted in the DF-R molecule are 2-oxa-4,6,9-triaza-cyclopenta­[ b ]­naphthalene resulting in DF-M1 , thia-4,6,9-triaza-cyclopenta­[ b ]­naphthalene to develop DF-M2 , [1,2,5]­thiadiazolo­[3,4- d ]­pyridazine to develop DF-M3 , 3-methoxy-thiophene to fabricate DF-M4 , 4,6-dimethyl-thieno­[3,4- b ]­thiophene-2-carboxylic acid methyl ester to form DF-M5 , and 3,4-dihydro-2 H -thieno­[3,4- b ]­[1,4]­dioxepine to fabricate DF-M6 . The insertion of six different π-spacers between the core and acceptors of the DF-R molecule has a prominent effect on optoelectronic attributes, electron and hole RE, and photovoltaic (PV) performance of all designed molecules.…”
Section: Introductionmentioning
confidence: 99%
“…4,7-Dihalogen-substituted 2,1,3-benzochalcogenadiazoles and [1,2,5]chalcogenadiazolo [3,4c]pyridines (chalcogen = O, S, Se) are important precursors for the preparation of dyesensitized solar cells (DSSCs) and organic light-emitting diodes (OLEDs) [1][2][3]. Recently, it was found that 4,7-dibromo [1,2,5]thiadiazolo [3,4-d]pyridazine-one of the strongest electron-acceptor systems-can also be an efficient intermediate for photovoltaic materials [4][5][6]. Selenium and oxygen analogs of chalcogenadiazolopyridazines may also have interesting photovoltaic properties.…”
Section: Introductionmentioning
confidence: 99%